1990
DOI: 10.1007/bf00842785
|View full text |Cite
|
Sign up to set email alerts
|

Indium 111 leucocyte scintigraphy in abdominal sepsis Do the results affect management?

Abstract: We have studied the clinical utility of indium 111 autologous leucocyte scintigraphy retrospectively in 45 patients presenting with suspected intra-abdominal sepsis. The sensitivity was 95% (21/22) and the specificity was 91% (21/23). Some 34 of the studies (17 positive and 17 negative) were considered helpful in furthering patient management (76%) and 8, unhelpful (18%). In 3, the study results were misleading and led to inappropriate treatment. Indium 111 scintigraphy, whether positive or negative, provides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Nuclear Medicine. Older studies performed in the 1980s to 1990s suggested that gallium scans and indium and technetium leukocyte scans are useful in evaluating abdominal infections and abscesses when the CT scan is negative or equivocal [43][44][45]. However, it is important to recognize that CT technology has significantly advanced since these studies were published.…”
Section: Discussion Of Procedures By Variantmentioning
confidence: 99%
“…Nuclear Medicine. Older studies performed in the 1980s to 1990s suggested that gallium scans and indium and technetium leukocyte scans are useful in evaluating abdominal infections and abscesses when the CT scan is negative or equivocal [43][44][45]. However, it is important to recognize that CT technology has significantly advanced since these studies were published.…”
Section: Discussion Of Procedures By Variantmentioning
confidence: 99%
“…Furthermore, LS with whole body imaging can reveal unsuspected extraabdominal sites of infection [28]. It has also been reported that in intra-abdominal infection, LS was considered helpful in furthering patient management in 76% of cases [31]. However, false positive results are described in patients suspected of having infection in the early postoperative period due to non-specific postsurgical inflammatory uptake [39].…”
Section: Resultsmentioning
confidence: 94%
“…In the last 30 years, a large number of papers have reported satisfactory results on the use of LS in the diagnosis of abdominal abscess, the most relevant of which are reported in Table 1 [25][26][27][28][29][30][31][32][33][34][35][36][37][38]. This diagnostic tool is sensitive in detecting abdominal abscess in different locations except for the liver and spleen due to physiological localization of labeled cells in these organs [39].…”
Section: Resultsmentioning
confidence: 96%
“…The appropriate definition of the role of each procedure in diagnostic/therapeutic clinical algorithms is the next challenge. This process is on-going by the European Association of Nuclear Medicine (EANM) in collaboration with several other European societies and, as a result, several procedural and joint guidelines have been already published [261][262][263][264][265][266].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, WBC scintigraphy can reveal unsuspected extra-abdominal sites of infection [260,263]. WBC scan has been reported to be helpful in intra-abdominal infection patient management in 76% of cases [260,264]. False positive results have been described in the early postoperative period due to non-specific postsurgical inflammatory uptake [198,260].…”
Section: Abdominal Infection 231 Abdominal Abscessmentioning
confidence: 99%